Psikografis dan Religiusitas dalam Bertransaksi Pada BNI Syariah Makassar - Muhammad Fauzi Amiruddin; Muhammad Wahyuddin Abdullah (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This study aims to determine the influence of psychographic factors that include activity, interest and opinion, as well as the religiosity factor to the decision to transact at the BNI Syariah Makassar. This type of research is quantitative research with correlational approach. The data used are primary data through direct questionnaire distribution, using non probability sampling and accidental sampling technique, totaling 56 samples. The respondents of this research are customers who use BNI Syariah products, then the analysis technique used is multiple regression. The result of this study indicates that the variables of activity, interest, opinion, and religiosity simultaneously affect the decision to transact at BNI Syariah Makassar. Partially, this research indicates that the variable of activity, opinion, and religiosity have an effect on the transaction decision, while the interest variable has no effect to the transaction decision at BNI Syariah Makassar. The implication of this research is that transaction activity in syariah bank has become activity which often done by society because the products owned by BNI Syariah Makassar bank have been able to support the society activity. The Society opinion on BNI Syariah bank is also positive, and the existence of BNI Syariah bank has become a solution for people who have high level of religiosity. To evaluate the issue of the society interest, BNI Syariah Makassar Bank should maximize the Information and Promotion media to attract the public interest.